Korelasi Pendidikan Karakter dan Minat Rohani dengan Perilaku Siswa Pada Sekolah Menengah Teologi Kristen (SMATK)/ Sekolah Menengah Agama Kristen (SMAK) di Sumatera Utara - M. Fransiska Gultom; Thomson Siallagan; Resie VM Sinaga (Sekolah Tinggi Teologi Baptis Medan, 2022)
AbstractThis study aims to analyze the correlation of character education and spiritual interest with student behavior. This research was conducted in the North Sumatran SMTK/SMAK. The method used in quantitative correlation research. The sample in the research was 94 students. The research instrument used a questionnaire. The data analysis technique used normality test, homogeneity test, linearity test, and Pearson Bivariate correlation test. The results of the study: concluded as follows: First, Character Education is positively correlated with Student Behavior in North Sumatran SMTK/SMAK, but not very significant. Second, spiritual interest is positively correlated with student behavior in North Sumatran SMTK/SMAK, but not very significant. Third, PAK's Character Education and Spiritual Interests are jointly positively correlated with Student Behavior in North Sumatran SMTK/SMAK, but not significantly. Keywords: Character education, interests, spirituality, behavior, students